New Improvement For Existing Warehouse By Implementing Technology 3D - Khairul, Muhammad; Putri, Anastasya (Publika Bersama Nusantara, 2025)
Warehousing plays a critical role in supporting manufacturing and supply chain operations by ensuring efficient storage, accessibility, and distribution of materials and finished goods. An effective warehouse layout directly influences operational performance, reducing handling time and optimizing space utilization. This study focuses on designing an optimized warehouse layout for PT. ABC. The research employs a combination of interviews and direct observations as primary data collection methods, complemented by secondary data obtained through literature review. The improvement approach integrates the Dedicated Storage system and the 5S methodology to enhance organization, reduce waste, and maintain workplace discipline. Additionally, FlexSim software was utilized to develop two- and three-dimensional models, allowing for visualization and simulation of the proposed layout. Results indicate that the new design improves efficiency by positioning high-turnover items closer to input/output points, reducing travel distance, and increasing throughput. Furthermore, recommendations for material handling equipment and inventory management strategies, such as Reorder Point (ROP), Economic Order Quantity (EOQ), and Safety Stock (SS), are provided to support sustainable operations. This study highlights the importance of systematic warehouse design as a key driver for operational excellence in the manufacturing sector.